PENGARUH PUPUK NITROGEN DAN TINGGI MUKA AIR TANAH TERHADAP PERTUMBUHAN BINTIL AKAR, PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max (L.) Merrill) - , SUWARTO; Wahju Qamara MUGNISJAH; DIDY SOPANDIE; ABDUL KARIM MAKARIM (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
Pot experiments and laboratory analysis were conducted to determine the effect of N fertilization and level of water table treatments of wet soybean culture on nodule formation and seed yield of soybean. The pot experiment was conducted in Cibungbulang and laboratorium analysis, was at three different laboratories: Soil, Agronomy, and Pasture, Bogor Agricultural University, started on August, 1993 up to February, 1 994. Three factors to be evaluated, namely varieties (Lokon and Lompobatang), N fertilizer applications of 0, 140, and 280 mg pot -1 (equivalent to 0, 25, and 50 kg N ha -1), and the level of water tables of (control, -15 cm, -10 cm, and -5 cm below the soil surface). They were arranged in randomized complete design. The highest value of nodule dry weight of Lokon variety (0.707 p. was resulted from the plant grown under -15 cm water table without N fertilizer (0 mg N pot- ). Lompobatang highest value (1. 727g) on -10 cm water table and fertilized with 140 mg N pot -1. The increases of nodule dry weight by the treatment were 0.300 g (73.7%) for Lokon and 1. 134 g (194.5%) for Lompobatang, respectively compared to control. Both varieties showed highest value of seed weight per plant if grown under -15 cm water table and fertilized with 140 mg N pot -1. Compared to control media, respective increased seed weight per plant 1.94 g (12.9%) for Lokon and 5. 40 g (25.4%) for Lompobatang.